Comparison of Nasal Septum and Ear Cartilage as a Graft for Lower Eyelid Reconstruction. Issue 2 (March 2016) - Suga, Hirotaka; Ozaki, Mine; Narita, Keigo; Kurita, Masakazu; Shiraishi, Tomohiro; Ohura, Norihiko; Takushima, Akihiko; Harii, Kiyonori
Abstract : Abstract: In lower eyelid reconstruction, several types of grafts from the nasal septum, ear cartilage, buccal mucosa, and hard palate mucosa have been used for an inner layer of the lower eyelid, but there have been no studies comparing these grafts. The authors retrospectively reviewed our cases of lower eyelid reconstruction, and compared chondromucosal grafts from the nasal septum (N = 8) and ear cartilage grafts (N = 10) for an inner layer of the lower eyelid. The authors observed no significant difference in operative time, blood loss, or length of hospital stay between the "nasal septum" and "ear cartilage" groups. The final results were aesthetically and functionally satisfactory in both groups. In the nasal septum group, 1 patient suffered from perforation of the nasal septum and another patient suffered from nasal bleeding postoperatively. There were no donor site complications in the ear cartilage group. These findings indicate that both a chondromucosal graft from the nasal septum and an ear cartilage graft are good grafts for an inner layer of the lower eyelid. Regarding the donor site, however, an ear cartilage graft has the advantage of a lower complication rate.